PENGARUH PENGGUNAAN VIDEO PEMBELAJARAN YOUTUBE KIDS UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning motivation of fifth-grade students at SD Negeri 1 Mastur, which was caused by monotonous, teacher-centered learning. One proposed solution is the use of YouTube Kids, an application that provides child-friendly and visually engaging educational content. The purpose of this study was to examine the effect of using YouTube Kids learning videos on students' learning motivation. The research employed a quantitative approach with a pre-experimental design, namely the One Group Pretest-Posttest Design. The subjects were 22 fifth-grade students selected through purposive sampling. The research instrument was a learning motivation questionnaire with a Likert scale, tested for validity and reliability. The research stages included administering a pretest, applying the treatment using YouTube Kids videos, and conducting a posttest with questionnaires. Data were analyzed using descriptive statistics and inferential statistics with a One Sample t-Test at a 0.05 significance level. The results showed that the average score of students' learning motivation increased to 70.82 with a standard deviation of 2.86, categorized as